Pengaruh Terapi Zikir Terhadap Kesejahteraan Psikologis Pada Lansia - Endah Wulandari; H. Fuad Nashori (JIP (Jurnal Intervensi Psikologi), 2014)
This study has purposed to know about effect zikr therapy for psychological well-being (PWB) in elderly. Researcher take data in elderly community â€œGriya Sanggar Asriâ€ at Purwomartani, Kalasan, Sleman. The participants consist of 9 elderly and classified into two groups : the experimental group and the control group. The experimental group was given the zikr therapy while the control group did not get the treatment, but stand as a waiting list. The effectiveness of the interventions was evaluated by using a quasi experimental design with pretest analysis consist of posttest and follow up. Before administrating the therapy both of the two group was given RPWBS (ryffâ€™s psychological well-being scale). The data from the two groups were analyzed using U Mann Whitney Test. The result of this study was gathered from the pre test and post test that have the value of Z = 0,369 and p = 0,730 (p > 0,05) this show that there is no different in the level of psychological well-being between experimental group and the control group. Based on this result it can be concluded that the zikr therapy has no significant effect in psychological well-being, this is caused by interference in internal and external validity that canâ€™t be controlled by the researcher like diffusion and history.Â Keyword : zikr therapy, psychological well-being well-being (PWB), elderly.